Gastric Perforation Due to Yellow Oleander Poisoning: First Case Report in Humans (Indian Journal of Forensic Medicine & Toxicology, 2023)
Yellow oleander (Thevetia peruviana) is a commonly found shrub in India which produces multiple alkaloidswhich are cardiotoxic. Numerous cases of yellow oleander poisoning have been reported in humans. The spectrumof toxicity due to this plant ranges from nausea, vomiting, diarrhoea, electrolyte abnormalities and arrhythmiasin humans. No case of bowel necrosis due to yellow oleander has been reported in humans to the best of ourknowledge.We present a case of 45-year-old female with suicidal consumption of crushed yellow oleander seeds. The patientwas admitted and observed for arrhythmias. On day 2 of admission, she developed bloody stools, hematemesisand abdominal pain. Abdominal examination showed rigidity and per rectal examination showed blood-stainedmucoid stools. A CECT was done which showed findings suggestive of gastric necrosis with perforation. Thepatient was taken up for surgery and stomach was found to be gangrenous with a perforation at the greatercurvature. Total gastrectomy was performed. The post operative biopsy showed extensive transmural coagulativenecrosis of the stomach and lymphoplasmacytic infiltration of the submucosa.Necrosis of bowel has been reported in experimental settings in animals and in cattle poisoning but no reportedcase of stomach necrosis and perforation due to yellow oleander has been reported in humans. As yellow oleanderis a commonly used suicidal poison in Southern Asia, an eye needs to be kept out for gastrointestinal symptoms.We conclude with recommendations on management of yellow oleander poisoning in the light of these newmanifestations.
Keywords: Gastrectomy, Gastric Necrosis, Perforation Peritonitis, Poisoning, Thevetia peruviana, Total gastrectomy, Yellow oleander